Eu, repórter : narradores em primeira pessoa nas reportagens de Trip, Tpm e Rolling Stone - Igor Lage Araújo Alves (2015)
This study is meant to examine the first person narrator uses in contemporary journalistic stories published in three magazines specialized in culture and behavior: Trip, Tpm and Rolling Stone Brasil. From reading these publications, we identified four manifestations of the first person in the context of enunciation, which we take as categories of analysis for the development of our reflections. In a first movement, we study the stories in which the reporter-narrator gives us accounts of his own experiences, creating strongly subjective narratives, and we also look at narratives in which the first person comes up often discreetly, to denote a situation of co-presence among reporter and interviewee. Because they are estabilished in the statement of the reporter‘s presence, we approach these manifestations to testimony discussions taken in the fields of historiography and literary criticism, in order to identify elements that would form a testimonial rhetoric specific to the journalistic texts. After that, we explore the possibilities of the first person plural as a strategy for getting close to the reader. From reflections on the processes that define the formation of editorial identities of the media, we define the "we" of the reporter-narrator as a space in which the magazines can speak of themselves and speak directly to the reader, an attribute that would make this type of first person an important element of a language that is somehow typical of magazines. Finally, we turn our attention especially to the stories of Arthur Veríssimo in Trip as a way to think about the quality of authorship relations that can be articulated in journalistic stories. By the perceiving of a scenario in which the reporter‘s signature competes with the magazine's name, we reflect upon the ways in which the first-person narrator can set processes for the occupation of the author‘s position.